Endoscopic Third Ventriculostomy for Hydrocephalus Due to Unruptured Pineal AVM: Case Report and Review of the Literature - Tucker, Adam; Tamura, Yoji; Hanabusa, Kenichiro; Miyake, Hiroji; Tsuji, Masao; Ukita, Tohru; Ohmura, Takehisa (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Introduction Arteriovenous malformations (AVM) are considered to be static congenital lesions; however, a subset may possess dynamic pathophysiological capabilities of growth, regression or other morphological changes with time. We report on an adult patient harboring a pineal AVM who presented with progressive symptoms of obstructive hydrocephalus and was successfully treated by endoscopic third ventriculostomy (ETV). Clinical presentation This 63-year-old man was incidentally diagnosed 8 years previously with an asymptomatic unruptured pineal AVM and followed conservatively until he developed a progressive impairment in consciousness with gait apraxia and incontinence over a period of 2 months. Magnetic resonance imaging (MRI) revealed obstructive hydrocephalus due to nidal compression at the level of the aqueduct. Treatment by ETV resulted in resolution of neurological deficits and ventriculomegaly without evidence of complications at 18-months follow-up. Conclusion Treatment by ETV in adults with obstructive hydrocephalus due to deep pineal AVMs is a reasonable option in selected cases. A discussion of the pathological mechanisms and therapeutic options for this rare entity is presented.
Keywords: endoscopy; third ventriculostomy; vascular malformation; hydrocephalus.